ANALISIS INTERCARRIER INTERFERENCE (ICI) SISTEM OFDM-MIMO STBC PADA KANAL FREQUENCY SELECTIVE FADING - Diki Andriasmika, I Wayan; Diafari Djuni H, I.G.A.K.; Dewi Wirastuti, N.M.A.E. (Jurnal SPEKTRUM; Vol 6 No 1 (2019): Jurnal SPEKTRUM, 2019)
Wireless telecommunications requires high-speed access. One technique used to oWireless telecommunications requires high-speed access. One technique used to overcome multipath fading is Ortoghonal Frequency Division Multiplexing (OFDM). The weakness of OFDM occurs on the mobile channel due to time variations in the channel, giving rise to intercarrier interference (ICI). The aim of the study is to determine the effect of normalized carrier frequency offset on ICI and the effect of frequency selective fading tap channel. The simulation results show the system performance in calculating the Eb / N0 5 dB value that the greater the normalized carrier frequency offset (?), the worse the signal. The simulation results show the OFDM-MIMO system performance in calculating the Eb / N0 5 dB value that the greater the tap on the channel the worse the signal.vercome multipath fading is Ortoghonal Frequency Division Multiplexing (OFDM). The weakness of OFDM occurs on the mobile channel due to time variations in the channel, giving rise to intercarrier interference (ICI). The aim of the study is to determine the effect of normalized carrier frequency offset on ICI and the effect of frequency selective fading tap channel. The simulation results show the system performance in calculating the Eb / N0 5 dB value that the greater the normalized carrier frequency offset (?), the worse the signal. The simulation results show the OFDM-MIMO system performance in calculating the Eb / N0 5 dB value that the greater the tap on the channel the worse the signal.